SEJARAH ADAT PENGANTIN PONOROGAN DI KABUPATEN PONOROGO TAHUN 2008-2019 - Pratama, Kristian Aji (History Department, Faculty of Humanities, University of Jember, 2023)
This thesis examines the history of Ponoragan wedding customs in Ponorogo Regency in 2008-2019. The purpose of this study is to explain the history of the formation to the inauguration of the Ponoragan bridal custom in Ponorogo Regency and the existence of the Ponoragan bridal custom after it was nationally confirmed by the Central Leadership Council of the Indonesian Bridal Makeup Expert Association (HARPI)